(untitled) (diségno, 2020)
The Mappa Metallographica (45.5 x 70.5 cm) is part of La Hongrie et le Danube, a collection of twenty-seven cartographic tables drafted over a period of fifteen years to illustrate the orography, hydrography and metallurgy of the Hungarian stretch of the Danube [1]. (read more)